Papel do TERRA na regulação da manutenção dos telômeros e na senecência replicativa em Leishmania major - Assis, Luiz Henrique de Castro (Universidade Estadual Paulista (Unesp), 2024)
Leishmaniases affect millions nowadays. It is caused by more than twenty species of parasites of the Leishmania genus. Due to the lack of efficient treatment and disease control, many efforts have been made to uncover the parasite's biological peculiarities. Telomeres have been considered antiparasitic drug targets since they are crucial for genome maintenance and cell survival. In several eukaryotes, telomeres are transcribed in long ncRNA's, such as TERRA, which is likely to affect telomere regulation. In Leishmania, TERRA transcription seems to be controlled by the modified thymine Base J, which is 98% concentrated at telomeres. Base J blocks restriction enzyme digestion and is an epigenetic signal for RNA polymerase II transcription termination. Therefore, Base J can interfere with TERRA and telomere homeostasis. We created L. major cell lines depleted of base J by editing the genes encoding JBP1 and JBP2, which are involved in Base J synthesis. Although the double knockout of JBP1 (JBP1-/-) was lethal to the parasites, the double knockout of JBP2 (JBP2-/-) was successfully generated. JBP2-/- cells presented growth ratios different from wild-type parasites during continuous in vitro passages. Also, cell cycle analyses showed that JBP2-/- initially presented arresting in G2/M phases. After several passages, JBP2-/- cells changed their proliferation profile, returning to the control level and accumulating in the S phase of the cell cycle. When examined by optical microscopy, JBP2-/- cells in P7 did not show morphological differences. However, ultrastructural alterations such as intense cytosolic vacuolization, autophagosomes, blebs in the flagellum or flagellar pocket, and concentric membranal structures within the mitochondrion were detected by transmission electron microscopy. RTqPCR detected quantitative differences in TERRA mRNA expression in JBP2-/- cells that grew up to P21. They also showed down-regulation of mRNAs involved in DNA and telomere replication and damage repair, probably due to base J depletion, which triggers a readthrough of RNA pol II transcription termination. In addition, JBP2-/- cells also showed increased telomere length after a few passages, suggesting a new role for JBP2 in the parasite's telomere maintenance.
Depletion of base J in Leishmania major triggers alterations in TERRA expression and telomer lenght
Relatório final submetido à FAPESP referente a bolsa PD
Keywords: Teloemros; Leishmania; Base J